2010
DOI: 10.1007/s10072-009-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution positively correlates with daily stroke admission and in hospital mortality: a study in the urban area of Como, Italy

Abstract: Some current evidences suggest that stroke incidence and mortality may be higher in elevated air pollution areas. Our study examined the hypothesis of a correlation between air pollution level and ischemic stroke admission and in Hospital mortality in an urban population. Data on a total of 759 stroke admissions and 180 deaths have been obtained over a 4-year period (2000-2003). Five air ambient particles have been studied. A general additive model estimating Poisson distribution has been used, adding meteorol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 12 publications
0
32
0
1
Order By: Relevance
“…An interesting area for investigation will be the relationship of variations in life-style-related and demo-topographic factors and acute cardiovascular fatality in relation to air pollution. Over the last decade, the epidemiological studies have demonstrated potential deleterious effects of ambient air pollution on health and its relation to heart disease and stroke, including increased risk for triggering of acute cardiovascular events [36,37,38,39,40,41,42], hospital admission for acute exacerbation of patients with congestive heart failure [43], or ventricular arrhythmias [44]. Although the mechanisms have not been fully elucidated, current evidence suggests that alterations in hemodynamics [36,45], hemostatic factors [46,47], vasoconstriction [48], and autonomic function [49] may underlie the cardiovascular effects of air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting area for investigation will be the relationship of variations in life-style-related and demo-topographic factors and acute cardiovascular fatality in relation to air pollution. Over the last decade, the epidemiological studies have demonstrated potential deleterious effects of ambient air pollution on health and its relation to heart disease and stroke, including increased risk for triggering of acute cardiovascular events [36,37,38,39,40,41,42], hospital admission for acute exacerbation of patients with congestive heart failure [43], or ventricular arrhythmias [44]. Although the mechanisms have not been fully elucidated, current evidence suggests that alterations in hemodynamics [36,45], hemostatic factors [46,47], vasoconstriction [48], and autonomic function [49] may underlie the cardiovascular effects of air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified 18 studies, which fulfilled these criteria (Table 4). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ACUTE EFFECTS OF PARTICULATE MATTER EXPOSURE Although most studies on PM and cardiovascular diseases have been conducted in developed western countries, first impulses for epidemiologic research on IS came from South Korea and Taiwan. 15,22,25 An increase in PM by an interquartile range in Seoul was associated with a 3% higher IS mortality.…”
Section: Particulate Matter and Human Health Particulate Matter Is A mentioning
confidence: 99%
“…20,27,28 Only three results reached the level of significance. 14,16,25 This reveals limitations of comparing air pollution and its influence on health outcomes globally. The composition of PM varies dramatically dependent on pollution sources like car traffic or industry.…”
Section: Particulate Matter and Human Health Particulate Matter Is A mentioning
confidence: 99%
“…PM 2.5 , NO 2 , particulate matter with aerodynamic diameter r10 mm (PM 10 ), carbon monoxide (CO) and ozone are the most commonly observed pollutants associated with ischemic stroke admissions. [8][9][10][11][12][13] Our previous study found that increased levels of NO 2 and CO contributed to an increased incidence of ED visits for acute ischemic stroke among the elderly aged 65 years and older in the warm season. 12 The purpose of the present analysis is to examine 1) the validity of the AQHI in predicting morbidity risk for acute ischemic stroke; 2) the three pollutants (O 3 , PM 2.5 , NO 2 ) used for AQHI calculation, of which individual pollutants are most consistent with observed associations with the AQHI; and 3) whether observed associations are more pronounced in the elderly.…”
Section: Introductionmentioning
confidence: 98%